GROWTH OF COLLAGEN AND FIBROBLAST NETWORK IN DOGS WITH DERMATITIS POST ECOENZYME TREATMENT - Kadek Ferdy Agastia Dwi Pratama; I Nyoman Suartha; I Ketut Berata; Luh Made Sudimartini (Buletin Veteriner Udayana, 2024)
Alternative products have recently been growing rapidly in society, the existence of these products is also a way to support efforts to preserve the environment. Alternative products are often used as an alternative to disease therapy, as is the case with fermented products called ecoenzymes. The active ingredients contained in ecoenzymes have benefits as anti-inflammatory, anti-arthritis, antipyretic, hypoglycemic, anti-gastric ulcer, spermicidal, anti-fungal, antibacterial, diuretic, antimalarial, antitumor, and immunomodulator. This study aims to determine the role of ecoenzymes in the development process of collagen and fibroblast tissue in dogs suffering from Atopic Dermatitis skin disease. In this study, 5 swimming female dogs were tested aged 4 months to 6 months, which were divided into 2 groups with 2 different concentrations. The first group with 3 dogs treated with ecoenzyme baths with a concentration of 10% were bathed twelve times every three days. The second group with 2 dogs treated with ecoenzyme bathing was bathed with 10% ecoenzyme three times every three days, then a week after that the exoenzyme level was reduced to 2% and bathed four times once a week. The administration of this coenzyme was in the form of a bath with water mixed with ecoenzym, then observations were made microscopically on collagen and fibroblast tissue. In this study it was concluded that coenzyme could be an effective alternative treatment for treating atopic dermatitis characterized by the density of collagen and fibroblast tissue for 5 weeks of ecoenzym administration by bathing.